Josephson oscillation linewidth of ion-irradiated YBa2Cu3O7 junctions. (17th May 2016) - Sharafiev, A; Malnou, M; Feuillet-Palma, C; Ulysse, C; Febvre, P; Lesueur, J; Bergeal, N
Abstract: We report on the noise properties of ion-irradiated YBa2 Cu3 O7 Josephson junctions. This work aims at investigating the linewidth of the Josephson oscillation with a detector response experiment at ≃132 GHz. Experimental results are compared with a simple analytical model based on the Likharev–Semenov equation and the de Gennes dirty limit approximation. We show that the main source of low-frequency fluctuations in these junctions is the broadband Johnson noise and that the excess 1 f noise contribution does not prevail in the temperature range of interest, as reported in some other types of high- T c superconducting Josephson junctions. Finally, we discuss the interest of ion-irradiated junctions to implement frequency-tunable oscillators consisting of synchronized arrays of Josephson junctions.